2021
DOI: 10.4209/aaqr.210084
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Carbon Dioxide Emission and Energy Saving Obtained by Renovation of Building Envelope of Existing Residential Buildings

Abstract: Energy and environmental issues have become increasingly prominent, and reducing energy consumption in the construction industry is a key part of solving the energy consumption and carbon dioxide emissions problem of the whole society. The existing buildings in south Jiangsu region of China have large stocks and huge energy consumption and carbon dioxide emissions.An existing residential building in south Jiangsu region of China is selected as the study object to carry out energy-saving reconstruction of its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, Du et al [ 6 ] conducted comparative research on the carbon emissions of the building industry in multiple provinces of China and concluded that promoting low-carbon building technology and reducing high-carbon materials could reduce carbon emissions from the industry; Chen and Chen [ 5 ] studied the potential impact of coal substitution policy on carbon emission of the building industry in the 13th Five Year Plan period of China and concluded that the carbon emission would decline by 20 to 29%. The micro-level research [ 8 , 9 , 10 , 11 ] focuses on how to reduce carbon emissions of some specific buildings by changing materials, structures, construction mode, etc. For example, Geng et al [ 10 ] found that the carbon emissions of a building can be reduced by 0.16–2.85 t per unit using wood flooring instead of ceramic tiles; Chen et al [ 8 ] found that the CO 2 emissions of a case building can be reduced 86t per year by improving Thermal envelope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Du et al [ 6 ] conducted comparative research on the carbon emissions of the building industry in multiple provinces of China and concluded that promoting low-carbon building technology and reducing high-carbon materials could reduce carbon emissions from the industry; Chen and Chen [ 5 ] studied the potential impact of coal substitution policy on carbon emission of the building industry in the 13th Five Year Plan period of China and concluded that the carbon emission would decline by 20 to 29%. The micro-level research [ 8 , 9 , 10 , 11 ] focuses on how to reduce carbon emissions of some specific buildings by changing materials, structures, construction mode, etc. For example, Geng et al [ 10 ] found that the carbon emissions of a building can be reduced by 0.16–2.85 t per unit using wood flooring instead of ceramic tiles; Chen et al [ 8 ] found that the CO 2 emissions of a case building can be reduced 86t per year by improving Thermal envelope.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-level research [ 8 , 9 , 10 , 11 ] focuses on how to reduce carbon emissions of some specific buildings by changing materials, structures, construction mode, etc. For example, Geng et al [ 10 ] found that the carbon emissions of a building can be reduced by 0.16–2.85 t per unit using wood flooring instead of ceramic tiles; Chen et al [ 8 ] found that the CO 2 emissions of a case building can be reduced 86t per year by improving Thermal envelope. Note that this paper concerns the micro-level building carbon emission.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of thermal renovation is acute not only in Ukraine, this problem is solved with various scientific and technical approaches (Barahona, B.,2021;Fernandez-Luzuriaga, J., 2022;Li, H., 2022;Mehregan, M., 2022;Popescu, L. L., 2021) taking into account ethnic, economic and climatic features in many countries of the world (Echlouchi, K., 2022;Gonzalez-Caceres, A., 2022;Milovanovic, B., 2022;Ricci, M., 2022;Wu, H., 2022;Zhang, X., 2021). In addition to the energy-saving effect, thermal renovation measures reduce the negative impact on the environment by reducing carbon dioxide emissions into the atmosphere (Chen, R., 2021;Kalbasi, R., 2022;Nematchoua M. K., 2022).…”
Section: Introductionmentioning
confidence: 99%